Revolutionizing Environmental Remediation: Innovative Magnetic Systems for Efficient Arsenic, Antimony, and Phosphorus Removal from Potable Aqueous Samples. - Doblado Onieva, Álvaro; Muñoz-Garcia, Andrea; Sánchez-Trujillo, Irene; Montoro-Leal, Pablo; López-Guerrero, María del Mar; Vereda-Alonso, Carlos; Vereda-Alonso, Elisa Isabel (My University, 2024)
In this comprehensive study, we address the critical issues of environmental contamination by focusing on the remediation of arsenic (As) and antimony (Sb) as well as the efficient removal of phosphorus (P) from aqueous samples. The research begins with a groundbreaking approach to arsenic remediation, acknowledging its widespread presence in the Earth's crust and its highly toxic inorganic forms, particularly As(III). A novel magnetic solid phase extraction method utilizing magnetic nanoparticles (MNPs) and graphene oxide (GO) functionalized with [1,5-bis (2-pyridyl) 3-sulfophenylmethylene] thiocarbonohydrazide M@GOPS was developed. This system demonstrated remarkable efficiency, achieving 100% removal of As in less than 30 minutes from a potable water source with an initial concentration of 0.01 g/mL, as confirmed by inductively coupled plasma mass spectrometry (ICP MS). Simultaneously, the study extends its focus to antimony, emphasizing the incapacity of Drinking Water Treatment Plants (DWTP) to entirely eliminate Sb concentration in natural waters due to its toxicity. The same innovative magnetic material (M@GOPS) was employed for the adsorption of Sb, achieving a 50% removal in 60 minutes from a potable water source with an initial concentration of 0.001 g/mL. Graphite Furnace Atomic Absorption Spectrometry (GFAAS) was employed for Sb determination. Transitioning to another environmental concern, the study introduces a novel patented magnetic graphene oxide (M@GO) for the removal of phosphorus from wastewater. Recognizing the adverse effects of excessive phosphorus on aquatic ecosystems, the M@GO adsorbent showcased easy separation from treated water using a magnetic field. The Langmuir isotherm was identified as the thermodynamic adsorption model, emphasizing efficient removal. .
Keywords: Biorremediación; Remediation; Phosphorus; Arsenic; Antimony